2017
DOI: 10.1016/j.jaci.2016.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IL-17F/frequent exacerbator endotype in asthma

Abstract: IL-17-related cytokines expression was amplified in bronchial/nasal mucosa of neutrophilic asthma prone to exacerbation, suggesting a pathogenic role of IL-17F in FEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 49 publications
(68 reference statements)
4
95
0
Order By: Relevance
“…36 Elevated levels are associated with airway inflammation in mouse models and humans. 3739 The data from the WTC-exposed FDNY cohort is consistent with a Th-2 and Th-17 response predicting airway remodeling and reactivity. These data support further investigation of the innate Th-17 response to pulmonary irritants.…”
Section: Discussionmentioning
confidence: 54%
“…36 Elevated levels are associated with airway inflammation in mouse models and humans. 3739 The data from the WTC-exposed FDNY cohort is consistent with a Th-2 and Th-17 response predicting airway remodeling and reactivity. These data support further investigation of the innate Th-17 response to pulmonary irritants.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, our study may also be relevant to exacerbations of lung diseases, such as asthma. Higher numbers of neutrophils and Th17 cytokines were recently reported in the bronchial/nasal mucosa of severe asthmatics compared to mild asthmatics, and particularly in severe asthmatics who suffer frequent exacerbations 43, 44 . The presence of endotoxin in house dust in urban environments has been associated with asthma symptoms, use of asthma medications and wheezing 45 .…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that the levels of IL‐17A and IL‐17F in sputum are elevated in patients with asthma and that increased levels of IL‐17A are associated with neutrophilic inflammation, increased AHR, and steroid resistance . Ricciardolo et al . have reported that IL‐17F‐expressing cells are abundant in bronchus in severe asthma with frequent exacerbation.…”
Section: Role Of Th17 Cells In Allergic Airway Inflammationmentioning
confidence: 99%